Estudio y diseños geométrico y estructural de la vía El Naranjo - Nudillo que comunica al cantón pasaje con el cantón Chilla, provincia de El Oro (abscisa 0+000 - 5+000). - Matute Solano, Fulton Alexander (2015)
Roads as we know them today are often the old routes and improving existing roads since time ago. Through them it is possible to move all types of goods, raw materials and processed products belongings and moving people. Currently, there are ways that have not been perfected to provide safety and comfort to its users, preventing sites crossed by these routes are forced to lower their production yields in different ways, experiencing a cultural socio-economic backwardness, even which affects the development of a province and therefore a country. The project that I present is intended to provide the beneficiaries of a sector of the citizenship of the cantons of Passage and Chilla a useful and appropriate design of the Way "Studies and geometric designs and structural Via El Naranjo - Knuckle connecting to Canton passage with Chilla Canton province of El Oro Abscisa (0 + 000-5 + 000). "commensurate with the growth of the cantons in question.